Hubungan Antara Media Pembelajaran Online Dengan Hasil Belajar Kelas Viii.7 Dan Viii.8 Pada Kegiatan Ektrakulikuler Pramuka Di Smp Negeri 7 Padang - Dela Febrian; Wirdatul'aini Wirdatul'aini (Jurnal Family Education, 2022)
This exploration is persuaded by the low learning results of understudies in grades VIII.7 and VIII.8 in scout extracurricular activities at SMP Negeri 7 Padang, this is apparently in light of the fact that it has something to do with internet learning media. This review expects to portray the utilization of web based learning media and see the connection between web based learning media and learning results for grades VIII.7 and VIII.8 in scout extracurricular exercises at SMP Negeri 7 Padang. This examination was directed utilizing a quantitative methodology with a correlational sort. The populace in this review were 62 understudies of class VIII.7 and VIII.8 who partook in scout extracurricular exercises. Tests were taken involving the propotionate delineated arbitrary examining method upwards of 38 individuals. Information assortment strategies through circulating surveys. The information investigation method utilizes the rate and item second recipes. The outcomes showed that web based learning media as per understudies was classified as low and there was a huge connection between web based learning media and the learning results of class VIII.7 and VIII.8 students who participated in scout extracurricular activities at SMP Negeri 7 Padang. It is expected that scout extracurricular coaches will use online learning media because it is related to student learning outcomes and it is recommended for other researchers to be able to look for other variables that affect student learning outcomes in extracurricular activities.